The art Formation and its aesthetic role in the design of digital commercial advertising: سند فؤاد محمد (Al-Academy, 2021)
Digital commercial advertising depends on artistic formations to achieve attraction and arousal of attention, which is one of the most important communication factors that the designer seeks to achieve and is considered a key key to recognizing the beauty of the topic and its functional value. Reframe formal vocabulary. The research included the introduction and includes the research problem and the need for it, which focused on the following question: What is the aesthetic role of artistic formation in the design of commercial advertising?The aim of the research was: To reveal the aesthetic role of artistic formation in commercial advertising.It also included the importance of research and research boundaries, as well as defining terms. The theoretical framework came, and it was defined in two topics that included the first topic (technical formation and its aesthetic role in design) and the second topic (advertising and digital design) and the theoretical framework resulted in several indicators. The third topic was devoted to research procedures, as the research followed the descriptive approach and the method of content analysis for the purpose of monitoring phenomena by means of objective analysis for each model separately, to reach accurate results. The research community included 30 global digital advertising posters published on the Internet. 3 posters were chosen to provide the objective conditions related to the research goal. The fourth chapter contains the most important findings and conclusions.1- The aesthetic feeling is an inevitable result of the education process, awareness of the prevailing values, and the cultural norm.2- It resulted that the aestheticians compare historical developments with theoretical approaches to the arts and for several periods, they study types of art in relation to their physical, social and cultural environments